Clostridium butyricum improves the intestinal health of goats by regulating the intestinal microbial community - Zhang, Chengrui; Hou, Tingyi; Yu, Qingyuan; Wang, Jihong; Ni, Miao; Zi, Yunfei; Xin, Hangshu; Zhang, Yonggen; Sun, Yukun (Frontiers in Microbiology, 2022)
Clostridium butyricum, as a probiotic with a variety of active products, has been widely used to improve the intestinal health of humans and animals. Previous studies had demonstrated that Clostridium butyricum exhibited potential protective and positive effects in human disease research and animal production by producing a variety of beneficial substances, such as intestinal inflammation, the intestinal epithelial barrier, metabolic diseases, and regulation of the gut microbiota. Therefore, we hypothesized that dietary Clostridium butyricum supplementation could improve gut health in fattening goats by modulating gut microbiota. However, it is unclear whether Clostridium butyricum can reach the intestine through the rumen, so 15 healthy Albas goats were selected and randomly divided into 3 treatments with 5 replicates in each group. The groups were divided as follows: control group (CON: basal diet), rumen-protected Clostridium butyricum group (RPCB: basal diet plus 1.0 × 109 CFU/kg Clostridium butyricum coated with hydrogenated fat), and Clostridium butyricum group (RPCB: basal diet plus 1.0 × 109 CFU/kg Clostridium butyricum). The experiment was slaughtered after a 70-day growth test, and the jejunal mucosa and intestinal contents of the goats were collected to determin tight junction protein- related genes expression and 16S rDNA microbial sequencing analysis to evaluate the intestine health. The results showed that dietary supplementation with Clostridium butyricum significantly increased the expression of the Claudin-4 gene of the jejunal mucosa (P<0.05) and had a trend towards a significant increase in the Occludin gene (0.050.10). In addition, the relative fractionation of Clostridium and Clostridiaceae_unclassified in the gut microbiota at the genus level decreased significantly compared with controls (P<0.05). The results of the analysis of the level of Clostridium species showed that Clostridium butyricum only existed in the treatment group. And the correlation results showed that Occludin and Claudin-4 genes were positively correlated with Sharppea and Clostridium butyricum, and negatively correlated with Clostridium (P<0.05). Supplementing Clostridium butyricum in the diet did not significantly affect the intestinal immune function of goats, while regulation of the intestinal microbiota was associated with improving the intestinal epithelial barrier.